2020
DOI: 10.1021/acsami.9b22288
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Visible–Invisible Multiband Detection and Imaging Achieved Using High-Performance 2D MoTe2/MoS2 Semivertical Heterojunction Photodiodes

Abstract: Two-dimensional (2D) van der Waals (vdW) heterostructures herald new opportunities for conducting fundamental studies of new physical/chemical phenomena and developing diverse nanodevice applications. In particular, vdW heterojunction p−n diodes exhibit great potential as highperformance photodetectors, which play a key role in many optoelectronic applications. Here, we report on 2D MoTe 2 /MoS 2 multilayer semivertical vdW heterojunction p−n diodes and their optoelectronic application in self-powered visible−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 37 publications
3
71
0
Order By: Relevance
“…[ 11–15 ] Noticeably, TMDs such as MoS 2 , WS 2 , MoSe 2 and WSe 2 possessing a moderate band gap range of 1.3–2.0 eV and smooth surface can be artificially stacked to form van der Waals heterostructures. [ 15 ] Therefore, a breaking number of novel 2D TMDs and other layered material hetero‐structure (such as MoTe 2 /MoS 2 , [ 16 ] WS 2 /MoS 2 [ 17 ] ) based self‐driven photodetectors because of photovoltaic effect are studied in these years. [ 18–21 ] By contrast, ambipolar WSe 2 , BP, and unipolar MoS 2 lateral or vertical homostructure comprised of P and N‐type doping part can be achieved through the local split gates, surface chemical doping and thickness engineering.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11–15 ] Noticeably, TMDs such as MoS 2 , WS 2 , MoSe 2 and WSe 2 possessing a moderate band gap range of 1.3–2.0 eV and smooth surface can be artificially stacked to form van der Waals heterostructures. [ 15 ] Therefore, a breaking number of novel 2D TMDs and other layered material hetero‐structure (such as MoTe 2 /MoS 2 , [ 16 ] WS 2 /MoS 2 [ 17 ] ) based self‐driven photodetectors because of photovoltaic effect are studied in these years. [ 18–21 ] By contrast, ambipolar WSe 2 , BP, and unipolar MoS 2 lateral or vertical homostructure comprised of P and N‐type doping part can be achieved through the local split gates, surface chemical doping and thickness engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the photodiode delivers a V oc of 0.3-0.4V in the NIR region due to the vdW bandgap of 0.67 eV. [250] Lee et al have demonstrated a multifunctional electronic device composed of SnSe 2 /MoTe 2 heterostructures with type-III band alignment (broken band alignment), which is different from the reports mentioned earlier (that are mostly based on type-II band alignment). With the calculated junction barrier of 1.4 eV, the device responds well to the 811 nm laser and exhibits detectivity of 7.5 × 10 12 Jones, in which the photocurrent is a result of FN tunneling caused by the interband transitions.…”
Section: Tmdc/tmdc Heterostructuresmentioning
confidence: 74%
“…Furthermore, the photodiode delivers a V oc of 0.3–0.4V in the NIR region due to the vdW bandgap of 0.67 eV. [ 250 ] Lee et al. have demonstrated a multifunctional electronic device composed of SnSe 2 /MoTe 2 heterostructures with type‐III band alignment (broken band alignment), which is different from the reports mentioned earlier (that are mostly based on type‐II band alignment).…”
Section: D Heterostructures For Ir Detectionmentioning
confidence: 92%
“…Ahn et al reported the optoelectronic application of a 2D MoTe 2 /MoS 2 2D vdWh with a wide spectrum detector (see Figure 7). [81] The developed MoTe 2 /MoS 2 photodiode exhibited wide spectrum photoelectric detection at wavelengths of 405-1310 nm, with a significant linear dynamic range of 130 dB in the range of 10% optical power density and 5 to 1 W cm −2 in photovoltaic mode.…”
Section: Photodetectorsmentioning
confidence: 99%